Bright Solid‐State Emission of Disilane‐Bridged Donor–Acceptor–Donor and Acceptor–Donor–Acceptor Chromophores. (28th January 2016) - Shimada, Masaki; Tsuchiya, Mizuho; Sakamoto, Ryota; Yamanoi, Yoshinori; Nishibori, Eiji; Sugimoto, Kunihisa; Nishihara, Hiroshi
Abstract: The development of disilane‐bridged donor–acceptor–donor (D‐Si‐Si‐A‐Si‐Si‐D) and acceptor–donor–acceptor (A‐Si‐Si‐D‐Si‐Si‐A) compounds is described. Both types of compound showed strong emission ( λ em =ca. 500 and ca. 400 nm, respectively) in the solid state with high quantum yields ( Φ : up to 0.85). Compound4 exhibited aggregation‐induced emission enhancement in solution. X‐ray diffraction revealed that the crystal structures of2, 4, and12 had no intermolecular π–π interactions to suppress the nonradiative transition in the solid state.